Demonstration of a novel, polyaniline film-coated composite membrane as an efficient separator for microbial fuel cells operated in the long-term - Szabolcs Szakács; László Koók; Zbynek Pientka; Miroslav Otmar; Jan Zitka; Libuše Brožová; Wojciech Kujawski; Tamás Rózsenberszki; Adrienn Fitos-Boros; Ahmed Bahaa; Kyu-Jung Chae; Nándor Nemestóthy; et al. (Chemical Engineering Journal Advances, 2025)
Membrane separators in microbial fuel cells (MFCs) affect mass transport, internal losses, anodic biofilm development and thus, overall MFC performance. In this work, a novel composite membrane was fabricated by coating a commercial ultrafiltration (UF, 10 kDa) membrane with a conductive polyaniline (PANI) layer via cross-linking. The PANI membranes were thoroughly characterized using scanning electron microscopy (SEM), atomic force microscopy (AFM), and water permeance tests, confirming successful and uniform coating. Long-term MFC experiments (>100 days) were conducted using acetate as sole substrate, comparing the efficiency of PANI-coated separator with the control UF membrane. PANI-MFCs demonstrated enhanced electrochemical performance, with up to two-fold peak current densities and nearly threefold Coulombic efficiencies. Electrochemical impedance spectroscopy revealed a marked reduction in diffusion resistances in PANI-MFCs. Cyclic voltammetry indicated the presence of multiple redox system in the anodic biofilms in PANI-MFCs, while UF-MFC showed one well-defined peak pair. 16S rRNA amplicon sequencing showed that UF and PANI lead to different microbial composition in the anodic biofilms, and that the PANI membranes facilitated colonization by electroactive microbes such as the genera Geobacter, Hydrogenophaga, and Thauera. Overall, this study demonstrated the applicability of PANI-coated UF membranes as effective and low-cost separators in MFCs, offering both improved energy recovery and favorable bioelectrochemical activity in long term.